Identification and Cloning of Genes Involved in Specific Desulfurization of Dibenzothiophene by Rhodococcus sp. Strain IGTS8 - Denome, Sylvia A. (1993)
The gram-positive bacterium Rhodococcus sp. strain IGTS8 is able to remove sulfur from certain aromatic compounds without breaking carbon-carbon bonds. In particular, sulfur is removed from dibenzothiophene (DBT) to give the final product, 2-hydroxybiphenyl. A genomic library of IGTS8 was constructed in the cosmid vector pLAFR5, but no desulfurization phenotype was imparted to Escherichia coli. Therefore, IGTS8 was mutagenized, and a new strain (UV1) was selected that had lost the ability to desulfurize DBT. The genomic library was transferred into UV1, and several colonies that had regained the desulfurization phenotype were isolated, though free plasmid could not be isolated. Instead, vector DNA had integrated into either the chromosome or a large resident plasmid. DNA on either side of the inserted vector sequences was cloned and used to probe the original genomic library in E. coli. This procedure identified individual cosmid clones that, when electroporated into strain UV1, restored desulfurization. When the origin of replication from a Rhodococcus plasmid was inserted, the efficiency with which these clones transformed UV1 increased 20- to 50-fold and they could be retrieved as free plasmids. Restriction mapping and subcloning indicated that the desulfurization genes reside on a 4.0-kb DNA fragment. Finally, the phenotype was transferred to Rhodococcus fascians D188-5, a species normally incapable of desulfurizing DBT. The mutant strain, UV1, and R. fascians produced 2-hydroxybiphenyl from DBT when they contained appropriate clones, indicating that the genes for the entire pathway have been isolated.